Glycolysis-mediated control of blood-brain barrier development and function. (July 2015) - Salmina, Alla B.; Kuvacheva, Natalia V.; Morgun, Andrey V.; Komleva, Yulia K.; Pozhilenkova, Elena A.; Lopatina, Olga L.; Gorina, Yana V.; Taranushenko, Tatyana E.; Petrova, Lyudmila L.
Graphical abstract: Highlights: Control of barriergenesis is provided by glycolysis and is developmentally regulated. Pro- or antiangiogenic microenvironment is established due to lactate production. Astroglial and endothelial cells regulate lactate transport within the neurovascular unit. Reciprocal changes in astroglial and endothelial glycolysis control blood-brain barrier functioning. Abstract: The blood-brain barrier (BBB) consists of differentiated cells integrating in one ensemble to control transport processes between the central nervous system (CNS) and peripheral blood. Molecular organization of BBB affects the extracellular content and cell metabolism in the CNS. Developmental aspects of BBB attract much attention in recent years, and barriergenesis is currently recognized as a very important and complex mechanism of CNS development and maturation. Metabolic control of angiogenesis/barriergenesis may be provided by glucose utilization within the neurovascular unit (NVU). The role of glycolysis in the brain has been reconsidered recently, and it is recognized now not only as a process active in hypoxic conditions, but also as a mechanism affecting signal transduction, synaptic activity, and brain development. There is growing evidence that glycolysis-derived metabolites, particularly, lactate, affect barriergenesis and functioning of BBB. In the brain, lactate produced in astrocytes or endothelial cells can be transported to the extracellular space via monocarboxylate transporters (MCTs), and may act on the adjoining cells via specific lactate receptors. Astrocytes are one of the major sources of lactate production in the brain and significantly contribute to the regulation of BBB development and functioning. Active glycolysis in astrocytes is required for effective support of neuronal activity and angiogenesis, while endothelial cells regulate bioavailability of lactate for brain cells adjusting its bidirectional transport through the BBB. In this article, we review the current knowledge with regard to energy production in endothelial and astroglial cells within the NVU. In addition, we describe lactate-driven mechanisms and action of alternative products of glucose metabolism affecting BBB structural and functional integrity in developing and mature brain.